Pannexin-1 channels and their emerging functions in cardiovascular diseases - Li, Lanfang; He, Lu; Wu, Di; Chen, Linxi; Jiang, Zhisheng (Acta biochimica et biophysica Sinica, 2015)
Pannexin-1, Pannexin-2, and Pannexin-3 are three members of the Pannexin family of channel-forming glycoprotein. Their primary function is defined by their ability to form single-membrane channels. Pannexin-1 ubiquitously exists in many cells and organs throughout the body and is specially distributed in the circulatory system, while the expressions of Pannexin-2 and Pannexin-3 are mostly restricted to organs and tissues. Pannexin-1 oligomers have been shown to be functional single membrane channels that connect intracellular and extracellular compartments and are not intercellular channels in appositional membranes. The physiological functions of Pannexin-1 are to link to the adenosine triphosphate efflux that acts as a paracrine signal, and regulate cellular inflammasomes in a variety of cell types under physiological and pathophysiological conditions. However, there are still many functions to be explored. This review summarizes recent reports and discusses the role of Pannexin-1 in cardiovascular diseases, including ischemia, arrhythmia, cardiac fibrosis, and hypertension. Pannexin-1 has been suggested as an exciting, clinically relevant target in cardiovascular diseases.